Pelaporan Kegiatan Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat Berbasis Android - Noviar Elga, Riko; Marlina, Marlina; Hasnawati, Hasnawati (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
Bhabinkamtibmas in its work area often faces various challenges in reporting situations and activities. As the spearhead of the police, Bhabinkamtibmas is responsible for maintaining security and order at the village or sub-district level, as well as building effective communication with the community. This research aims to create an application that can help Bhabinkamtibmas in reporting situations and conditions in their work areas more easily and effectively. This research uses qualitative methods. This research uses analysis of existing systems, application design, testing, and implementation, and data collection is carried out by direct observation and literature study from relevant sources. This application makes it easier for Bhabinkamtibmas to manage and report its activities, so that supervision and community service tasks can be carried out in a more structured and transparent manner.